2020
DOI: 10.1159/000508001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurements of Intracranial Structures in Growth-Restricted Neonates with Fetal Blood Flow Redistribution: A Pilot Observational Study

Abstract: <b><i>Background:</i></b> Fetal growth restriction (FGR) is associated with neonatal and long-term neuro-morbidity. Preferential redistribution of blood flow to the brain is a common antenatal adaptation in FGR. The impact of this “brain sparing,” which may signify severity of FGR, on the growth of brain structures has not been studied. <b><i>Aim:</i></b> To compare corpus callosum (CC), cerebellar, and ventricular measurements of FGR neonates with evidence of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…When placental dysfunction continues, intrauterine stress and hypoxemia get prolonged and severe, cerebral perfusion shifts to brain structures that is fed by the middle cerebral artery. 2 The decreased resistance 13 In a study by Koning et al, shorter CCL and CCLF were observed in FGR and these measurements might have been important in the neurodevelopmental status of infants born with FGR. 16 However, due to the lack of information related to the umbilical cord blood samples in the present study, the authors could not confirm intrauterine hypoxia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…When placental dysfunction continues, intrauterine stress and hypoxemia get prolonged and severe, cerebral perfusion shifts to brain structures that is fed by the middle cerebral artery. 2 The decreased resistance 13 In a study by Koning et al, shorter CCL and CCLF were observed in FGR and these measurements might have been important in the neurodevelopmental status of infants born with FGR. 16 However, due to the lack of information related to the umbilical cord blood samples in the present study, the authors could not confirm intrauterine hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…12 Previous studies using fetal magnetic resonance imaging and ultrasonographic scanning have detected a smaller CC in preterm and/or growth-restricted fetuses. 13,14 Fastigium can be defined as a thin roof plate of the fourth ventricle and one the crucial marker of the normal posterior fossa development. 15 Koning et al, also demonstrated that fetuses with FGR and neonates born with FGR were associated with decreased growth of CC-fastigium length (CCFL), which is a valuable marker of diencephalon and mesencephalon development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are similar to those of a pilot study on cUS measurements in singletons, reporting that FGR neonates with antenatal brain sparing have a smaller corpus callosum and cerebellum 4 . In our study, no additional effect of brain sparing was found.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic adaptation of the brain to suboptimal growth conditions can be detected antenatally as ‘brain sparing’, a redistribution of blood flow to the brain indicated by a decreased cerebroplacental ratio (CPR) 3 . Despite this supposedly protective mechanism, deficits in brain structures are prevalent in FGR singletons, and include reduced intracranial volume, corpus callosal size and cerebellar diameter 4 , 5 . These structural deficits are known to have significant consequences for brain function in childhood, being associated with, for example, lower cognitive test scores and impaired motor skills 6 .…”
Section: Introductionmentioning
confidence: 99%